FACIAL REJUVENATION WITH THE 3S VERTICALIZATION TECHNIQUE: CASE REPORT - Alexandre Ramos Do Couto, Leonardo; Carolina Nogueira Bientinez Basile, Ana (Health and Society, 2022)
The natural aging process is inevitable, and cannot be stopped, but it can be considerably delayed nowadays, in view of the numerous techniques that contribute to rejuvenation. Aging is the result of the interaction of changes that occur in the five anatomical facial layers: skeleton, ligaments, muscles, adipose tissue and skin. To target them, combined interventions in these layers are needed. The 3S verticalization technique comes with the purpose of returning the face to more balanced proportions, restoring facial harmony. This technique is a set of non-surgical procedures that involves the use of botulin toxin, polydioxanone wires (PDO) and hyaluronic acid. This work aims to describe a case report, in which facial rejuvenation was sought using the 3S technique, in order to confirm its effectiveness and safety. This is a 35-year-old patient who presented lines of expression in the upper third, slight flabbiness in the middle and lower third, starting to square the face, well-marked nasolabial folds and a drop in the nasal tip. In this study, we concluded that the 3S verticalization technique proved to be effective, with visibly satisfactory results, being effective, since that well indicated and well executed. It is a safe technique, as long as the professional has the appropriate training to perform all the procedures described in the same.